Models and outcomes of work-based learning and industry collaboration for vocational teacher professional development: a systematic literature review - Satria Yudhistira; Nurhasan Syah; Bambang Heriyadi; Risfendra; Muhammad Akbar (Indonesian Institute for Counseling, Education and Theraphy, 2026)
Vocational teachers are expected to continuously develop pedagogical and industry-relevant competencies to address rapid technological and workforce changes. However, evidence regarding the effectiveness of work-based learning and industry collaboration in supporting vocational teacher professional development remains fragmented across different educational contexts. This study synthesizes empirical evidence on vocational teacher professional development through a Systematic Literature Review (SLR). Following the PRISMA 2020 guidelines, relevant studies were retrieved from the Scopus database using predefined search strategies and screened according to predetermined inclusion and exclusion criteria. therteen empirical studies published between 2020 and 2025 were included and analyzed using thematic synthesis. The findings indicate that work-based learning, workplace immersion, teaching factory, and industry collaboration consistently strengthen teachers’ pedagogical, technical, and professional competencies while improving curriculum relevance. Nevertheless, institutional support, funding, and sustainable school–industry partnerships remain key implementation challenges. These findings provide an evidence-based foundation for developing sustainable vocational teacher professional development programs.